Peran Tari Remo Gagrak Anyar untuk Menanamkan Disiplin Diri pada Anak Di SDN Rangkah I Surabaya - Hesthi Putri Budi Rahayu; Aditya Dyah Puspitasari (Yayasan Arrahman Nahdlatul Wathan, 2024)
Students who lack discipline are the teacher's responsibility to overcome this problem. One way to discipline students is through the new remo gagrak dance. This research aims to describe the role of the new Remo Gagarak dance in instilling self-discipline in children at SDN Rangkah I Surabaya. The research uses descriptive qualitative methods with observation, interview and documentation techniques. The results of the research show: 1) Self-discipline in the rules of the new Remo Gagarak dance movements in variations 1, 2, and 3, wiraga (hand, foot and head movements), wirama (matching movements with music), and wirasa (facial expressions) has been achieved. Good. 2) Self-discipline in socializing between students when dancing the new Remo Gagarak dance can be seen in maintaining movements so that they are appropriate, rhythmic, unified and harmonious. Students also reprimand, advise, and practice movements if a friend makes a mistake. 3) Self-discipline in training equipment can be seen from students who bring long-sleeved shirts, long leggings and sash. In conclusion, the students' self-discipline in the new Remo Gagarak dance movements was visible and met the indicators of self-discipline.